PROTEIN CONTENT AND COLOR OF GREEN MACROALGAE Ulva lactuca (L.) ON SOAKING TIME AND DRYING METHOD - Sefrienda, Ardiba Rakhmi; Novianty, Hilda; Jasmadi, Jasmadi; Suryaningtyas, Indyaswan Tegar; Poeloengasih, Crescentiana Dewi; Kumayanjati, Bayu; Permadi, Sandi; Setyono, Dwi Eny Djoko (Universitas Sebelas Maret (UNS), 2022)
The green macroalgae Ulva lactuca (L.) is a potential alternative protein source. This study investigates the effect of soaking and different drying methods on the protein and color quality of U. lactuca. Moisture and ash content, color, and protein content, i.e., crude protein, in vitro protein digestibility, and protein solubility of the seaweed were determined. In its conduct, fresh U. lactuca was soaked in fresh water for various soaking times (0, 1, 2, and 3 h). Soaking U. lactuca with the highest protein digestibility was selected for further drying method investigation, i.e., sun-drying, shade-drying, and oven-drying at 40°C. The results reveal that soaking treatment did not affect protein quality significantly, but there was a significant effect of soaking treatment on the ash content and color quality of U. lactuca. Among the drying method, sun drying and oven drying resulted in higher in-vitro protein digestibility and protein solubility compared to shade drying.